NASICON‐Based Solid State Li‐Fluoride Conversion Batteries Enabled by Constructing a Fluorine‐Rich Trap for Ti4+. Issue 12 (5th February 2023) - Gu, Yuping; Hu, Jiulin; Lai, Chuanzhong; Li, Chilin
Abstract: The application of solid‐state Li metal batteries based on NASICON‐type Li(1+ x ) Al x Ti(2‑ x ) (PO4 )3 (LATP) electrolytes has been hindered by the interface instability, originating from the spontaneous Ti 4+ reduction reaction between LATP and Li. Here, a mesoporous fluorination interlayer based on high‐surface‐area AlF3 is proposed to improve the stability and compatibility of the LATP/Li interface and enable the reversible operation of NASICON‐type Li||FeF3 conversion batteries. The high Lewis acidity and porosity in the interlayer can buffer the volume evolution, increase the Li‐ion transference number and promote the formation of LiF domains. Time‐of‐flight secondary‐ion mass spectroscopy (ToF‐SIMS) proves the in situ construction of an F‐rich trap zone for Ti 4+, which can pin the easily‐reduced Ti 4+ in LATP and retard its conversion to Ti 3+ during the electrochemical process. An electro‐fusion process at the LATP/Li interface occurs and successfully welds the solid electrolyte, AlF3 interlayer, and anode into a whole to mitigate the anode resistance, guaranteeing the fast interface migration of Li + . The corresponding Li||Li symmetric cells exhibit a stable cycling performance with small voltage hysteresis for at least 500 h. The ceramic‐type solid‐state Li‐Fe‐F cells modulated by the F‐rich transition layer can deliver a high capacity of 696.7 mAh g −1 and show a good cyclability of the conversion reaction. Abstract : A mesoporous fluorination interlayer based on high‐surface‐area AlF3 is proposed to improve the stability and compatibility of LATP/Li interface and enable the reversible operation of NASICON‐type Li||FeF3 conversion batteries. A F‐rich trap zone for Ti 4+ is in situ constructed, and it can pin the easily‐reduced Ti 4+ in LATP and retard its conversion to Ti 3+ during electrochemical process.